The association between HbA1c/HDL-C and the incidence of cardiometabolic multimorbidity in middle-aged and elderly adults: Results from the China Health and Retirement Longitudinal Study - Yuan Zeng; Lin Lu; Wenwu Zheng; Gong Chen (PLoS ONE, 2025)
Background Cardiometabolic multimorbidity (CMM) refers to a cluster of metabolic and cardiovascular diseases, including stroke, diabetes, and cardiovascular diseases. Glycated hemoglobin (HbA1c) and high-density lipoprotein cholesterol (HDL-C) are widely used to assess glucose metabolism and lipid metabolism disorders, respectively, given their close association with the onset of diabetes and cardiovascular diseases. This study aimed to investigate the association between the HbA1c/HDL-C ratio and the incidence of newly diagnosed CMM in individuals aged 45 and older, using data from the China Health and Retirement Longitudinal Study (CHARLS) database. Method Our study utilized data from the CHARLS database from 2011 to 2018. A multivariate logistic regression model was established to determine the association between the cumulative average HbA1c/HDL-C (2011–2015) and the incidence of newly diagnosed CMM (2015–2018). Besides, a multivariable-adjusted restricted cubic spline (RCS) curve, stratified analysis, and interaction tests were conducted to evaluate the relationship between HbA1c/HDL-C and CMM. Results Our longitudinal analysis included 4,225 participants, with 716 new cases of CMM identified over a 7-year follow-up period. A positive association was observed between the HbA1c/HDL-C ratio and the incidence of CMM. In the fully adjusted model, the highest quartile of HbA1c/HDL-C (Q4) exhibited the highest risk of CMM (OR = 1. 08, 95% CI: 1. 04–1. 12). The association between the HbA1c/HDL-C ratio and CMM incidence was consistent in all subgroups except for education level. Stratified analysis showed no significant interaction between the HbA1c/HDL-C ratio and factors such as age, gender, marital status, education level, residence, smoking status, drinking status, and body mass index (BMI). Conclusion A significant linear relationship exists between the HbA1c/HDL-C ratio and the risk of CMM. Accordingly, the HbA1c/HDL-C ratio may be an independent risk factor for CMM. Among middle-aged and older adults, monitoring and managing HbA1c/HDL-C levels may aid in identifying individuals at high risk of developing CMM.